1994
DOI: 10.1177/019262339402200210
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Death in Rodent Toxicity and Carcinogenicity Studies

Abstract: Peto test procedures for the statistical evaluation of carcinogenicity studies require that each tumor in an animal that died intercurrently (or was sacrificed in extremis) be classified as either fatal, probably fatal, incidental, or probably incidental. There is considerable controversy as to whether or not the cause of death can be established with accuracy in rodent studies. In the present article, the causes of death or ill-being as found in 10 consecutive carcinogenicity studies--5 studies with 2400 OFA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 13 publications
1
29
0
Order By: Relevance
“…Although the fatal neoplastic lesions were distributed in this study as described in previous reports of carcinogenicity studies using Sprague-Dawley derived rats [2,6], the incidence of fatal neoplasms was relatively low in this study, probably because there were more cases of chronic progressive nephropathy causing earlier death. The tumor incidences in males and females of both groups in this study were comparable with those reported by Muraoka et al [10], but much higher than in Prejean et al [12] who reported incidences of 34% and 58% in males and females, respectively.…”
Section: Discussionmentioning
confidence: 44%
“…Although the fatal neoplastic lesions were distributed in this study as described in previous reports of carcinogenicity studies using Sprague-Dawley derived rats [2,6], the incidence of fatal neoplasms was relatively low in this study, probably because there were more cases of chronic progressive nephropathy causing earlier death. The tumor incidences in males and females of both groups in this study were comparable with those reported by Muraoka et al [10], but much higher than in Prejean et al [12] who reported incidences of 34% and 58% in males and females, respectively.…”
Section: Discussionmentioning
confidence: 44%
“…The 3 most common contributing causes of death in F344 rats are leukemia, pituitary gland tumors, and (for male rats) nephropathy (5,6). Rats fed the NTP-2000 had slightly decreased incidences of leukemia (feeding studies only), significantly decreased incidences of pituitary gland tumors, and perhaps most importantly, striking decreases in the incidence and severity of nephropathy (especially for males).…”
Section: Tumor Incidence Datamentioning
confidence: 99%
“…Factors influencing spontaneous tumor incidence are reviewed by several authors (Everett, 1984;Hardisty, 1985;Gopinath, 1994). However, most of this is lifetime data (Maita et al, 1988;Ettlin et al, 1994); therefore it was considered useful to obtain data on tumor occurrence in animals dying during their first year of life, since tumors observed in treated animals prior to completion of a study may pose problems in interpretation. This report is intended to establish a general profile of tumor occurrence in CD-1 mice and SD rats during the first 50 weeks of chronic toxicity/carcinogenicity studies.…”
Section: Introductionmentioning
confidence: 99%